PENGARUH PEMBERIAN VITAMIN B1, B6 DAN B12 TERHADAP KELELAHAN OTOT PETANI SAWIT DI GUNUNG TIMBUL - Nabilla Ayu Canthika Hairil Nabilla (Yayasan Pendidikan Medika Indonesia, 2020)
The aim of this study was to determine whether there was an effect of vitamins b1, b6, and b12 on muscle fatigue of oil palm farmers. This type of research is correlational pre-experimental research. The population of this study were all. Based on the above opinion, the population of this study were all of the Gunung Timbul oil palm farmers as many as 30 people. A sample of 12 people was obtained based on the criteria under the age of 18 with purposive sampling technique. Based on the results of the data analysis carried out, the lactic acid data before being given vitamins b1, b6, and b12 had a mean value of 6.3583, with a standard deviation of 1.54946, a max value of 8.30, and a min value of 3.50 with a sum value of 76.30. Lactic acid data after being given vitamins b1, b6, and b12, the mean value was 4.3417, with a standard deviation of 1.07150, a max value of 6.10, and a min value of 3.20, with a sum value of 52.10, data on lactic acid measurements before being given vitamins b1, b6, and b12 Asymp value = .812, this indicates that the data follows a normal distribution or is normally distributed. Lactic acid data after being given vitamins b1, b6, and b12 = 869 (p> 0.05), so this shows that the lactic acid data after massage follows a normal distribution or is normally distributed. From the results of the analysis of the table above, it can be seen that there is an effect of giving vitamins b1, b6, and b12 to the reduction of lactic acid levels in Gunung Timbul oil palm farmers. The sig value is 0.00 where if the p value is <0.05 then it is statistically said to have an effect.Based on the results of the data and discussion of this study, it can be concluded that there is an effect of vitamins b1, b6, and b12 on reducing levels of lactic acid in Gunung Timbul oil palm farmers. .